Identifikasi Penyebab Unmet Need KB Di Desa Pegayaman Kecamatan Sukasada Kabupaten Buleleng Tahun 2019 - Mertasari, Luh; Sulyastini, Ni Komang; Sugandini, Wayan (Akademi Kebidanan Bunga Husada Samarinda, 2021)
The incidence of family planning unmet needs in Indonesia continues to increase from year to year. Many women who do not need family planning. Pegayaman village ranks the largest unmet need incidence in Buleleng. There are 200 unmet needs whose cause has not been identified. The purpose of this study was to identify the factors causing the unmet need for family planning in Pegayaman. This type of research was descriptive with a survey method. The total sample was 200 women women. The study population was 200 people with a total sampling technique of the WUS population who did not have family planning. The data collection method was cross sectional and univariate analysis was carried out. The results of the study: it was identified that the age of the unmetned respondents was spread across the reproductive range of healthy and unhealthy, with the number of children 1-4 and lebih dari 4 people, experience using contraceptive methods once, and reasons for unmet need because many children had a lot of luck, belief, rarely had sexual intercourse and does not have the support of the husband.